2013
DOI: 10.1192/bjp.bp.112.113548
|View full text |Cite
|
Sign up to set email alerts
|

Treatment in a specialised out-patient mood disorder clinicv.standard out-patient treatment in the early course of bipolar disorder: randomised clinical trial

Abstract: Treatment in a specialised mood disorder clinic early in the course of bipolar disorder substantially reduces readmission to a psychiatric hospital and increases satisfaction with care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(181 citation statements)
references
References 37 publications
2
178
1
Order By: Relevance
“…The current RCT demonstrated that in people with a few episodes (1-7), PEd may have been more effective than PS against time to next depression episode and time to next bipolar episode. The result requires replication in a sample confined to people early in the course of BD; RCTs of psychological interventions compared to treatment as usual confined to participants early in the course of their illness report clinical and cost effectiveness (35,36). Previous RCTs of group psychoeducation versus group support may have shown a greater effect of group psychoeducation on time to the next bipolar episode than the current study because their sample recruited more participants in the early course of their illness (8,33).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The current RCT demonstrated that in people with a few episodes (1-7), PEd may have been more effective than PS against time to next depression episode and time to next bipolar episode. The result requires replication in a sample confined to people early in the course of BD; RCTs of psychological interventions compared to treatment as usual confined to participants early in the course of their illness report clinical and cost effectiveness (35,36). Previous RCTs of group psychoeducation versus group support may have shown a greater effect of group psychoeducation on time to the next bipolar episode than the current study because their sample recruited more participants in the early course of their illness (8,33).…”
Section: Discussionmentioning
confidence: 68%
“…Our results and the results of other recent psychological interventions (22,33,35,36) suggest that the optimal provision of structured psychological interventions such as PEd early in the course of bipolar disorder may have important benefits on the course of illness, and merits further research.…”
Section: Discussionmentioning
confidence: 85%
“…There is increasing evidence to suggest that, for a subgroup of patients, BD may be a neuroprogressive disease in which recurrences are associated with reductions in brain grey and white matter volumes, worsening cognitive impairment, a decrease in inter‐episodic recovery and functioning, a higher rate and severity of relapse, and a reduced rate of treatment response to both pharmacotherapy and psychotherapy 325. It is therefore important that comprehensive treatment be initiated even after a first episode 63. Effective maintenance treatment, early in the course of illness, has been shown to reverse cognitive impairment and preserve brain plasticity, particularly in those who remain episode free,326, 327 and may therefore lead to improved prognosis and minimization of illness progression 328.…”
Section: Maintenance Therapy For Bipolar Disordermentioning
confidence: 99%
“…58,82,83 In our opinion, early detection combined with helpful self-management and targeted psychosocial and drug treatment promises substantial benefits. To be economically sustainable, psychosocial protocols need to be standardised for settings that serve large numbers of patients and have few resources for clinician training.…”
Section: Future Directionsmentioning
confidence: 99%
“…90 Cognitive-behavioural therapy to treat depression has been adapted for patients with bipolar disorder with recognition that manic episodes are often associated with excessively optimistic thinking. 71 One randomised controlled trial 58 reported that patients who received 12-14 sessions of cognitive-behavioural therapy were less likely to have depressive episodes and had better social functioning than patients in routine care for 30 months. However, an effectiveness trial (n=252) comparing cognitivebehavioural therapy with treatment as usual in five UK community care centres found no advantage for cognitive-behavioural therapy over 18 months, except among patients with fewer than 12 previous episodes.…”
Section: Cognitive-behavioural Therapymentioning
confidence: 99%